La Educación en y para el tiempo libre - Machado Almanza, Juan Pablo (My University, 2018)
La investigación aborda la problemática de cómo contribuir a la formación del uso del tiempo libre. Se presentan acciones que contribuyen para la formación de esta cultura, teniendo como base los conceptos de cultura, recreación, recreación física, actividades físico-recreativas, tiempo libre, jóvenes, y comunidad. Se parte de la teoría a la práctica, que lleva a evaluar, el uso del tiempo libre y el fortalecimiento profesional en la esfera de recreación, basada en el diseño de acciones, sobre la base de educar en y para el tiempo libre. Resultando de gran aceptación y satisfacción, con reconocimiento institucional y comunitario.

The research addresses the problem of how to contribute to the formation of the use of free time. Actions that contribute to the formation of this culture are presented, based on the concepts of culture, recreation, physical recreation, physical-recreational activities, leisure time, youth, and community. It starts from theory to practice, which leads to evaluate, the use of free time and professional strengthening in the sphere of recreation, based on the design of actions, based on education in and for free time. Resulting in great acceptance and satisfaction, with institutional and community recognition.
The Education in and for the free time